Chapter Guerre, dirigisme, approvisionnement. Les marchandises de luxe, monnaie d’échanges alternative sous la Terreur - Coquery, Natacha (Firenze University Press, 2025)
From 1792 to 1795, the war absorbed half of the French state budget at a time when the fiscal situation was disastrous. The political authorities decided to set up a managed economy to support production, supply the armies and towns and limit the fall in the scrip. Under the authority of the comité de salut public, an alternative practice was organised - payment in kind: luxury manufactured goods in exchange for raw materials and necessities. The aim is to understand the logic at play: the role of neutral powers and French traders, the need for supplies, the unexpected revaluation of a specific sector of the French economy (luxury goods), and the balance between ideology and political pragmatism.